Spatial neglect treatment: The brain's spatial-motor Aiming systems. Issue 5 (28th May 2022) - Barrett, A. M.; Goedert, Kelly M.; Carter, Alexandre R.; Chaudhari, Amit
ABSTRACT: Animal and human literature supports spatial-motor "Aiming" bias, a frontal-subcortical syndrome, as a core deficit in spatial neglect. However, spatial neglect treatment studies rarely assess Aiming errors. Two knowledge gaps result: spatial neglect rehabilitation studies fail to capture the impact on motor-exploratory aspects of functional disability. Also, across spatial neglect treatment studies, discrepant treatment effects may also result from sampling different proportions of patients with Aiming bias. We review behavioural evidence for Aiming spatial neglect, and demonstrate the importance of measuring and targeting Aiming bias for treatment, by reviewing literature on Aiming spatial neglect and prism adaptation treatment, and presenting new preliminary data on bromocriptine treatment. Finally, we review neuroanatomical and network disruption that may give rise to Aiming spatial neglect. Because Aiming spatial neglect predicts prism adaptation treatment response, assessment may broaden the ability of rehabilitation research to capture functionally-relevant disability. Frontal brain lesions predict both the presence of Aiming spatial neglect, and a robust response to some spatial neglect interventions. Research is needed that co-stratifies spatial neglect patients by lesion location and Aiming spatial neglect, to personalize spatial neglect rehabilitation and perhaps even open a path to spatial retraining as a means of promoting better mobility after stroke.